Analisa Faktor-Faktor yang Mempengaruhi Prilaku Sedekah Harta Pada Karyawan PT. TELKOMSEL Tbk - Wahibul Minan; Indra -; Luqyan Tamanni (ILTIZAM Journal of Shariah Economics Research, 2021)
Charity behavior is related to the motivation, ethics, intensity, priority, object and nominal of charity. Charity behavior is influenced by several factors, including religiosity, charity knowledge, Islamic financial planning, altruism and involvement in spiritual organizations. The purpose of this study was to determine how much influence the factors of religiosity, knowledge of charity, Islamic financial planning, altruism and involvement in spiritual organizations have on the behavior of charity. The object of the research is the employees of PT. Telkomsel Tbk. with diverse demographic and socioeconomic characteristics. This research is a quantitative research using Structural Equation Model (SEM) with Partial Least Square (PLS) analysis technique with SmartPLS application. The results of this study indicate that the variables of religiosity and charity knowledge have no significant effect on the behavior of charity of wealth. While the variables of Islamic financial planning, altruism and involvement in spiritual organizations have a significant effect on the behavior of giving assets to employees of PT. Telkomsel Tbk.